1999
DOI: 10.1247/csf.24.247
|View full text |Cite
|
Sign up to set email alerts
|

Exocytotic Secretion of Toxins from Macrophages Infected with Escherichia coli O157.

Abstract: This study examined whether macrophages are involved in the development of pathogenicity in Shiga-like toxin (SLT)-producing enterohemorrhagic Escherichia coil (EHEC) O157:H7. Macrophages were infected with the bacteria, after which the macrophage culture medium showed a clear increase in toxicity in rats in vivo as well as in rat aortic endothelial cells in vitro. The increased toxicity resulted mainly from a rapid increase in the concentrations of SLT type I (SLT-I) and type II (SLT-II) and partly from an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…First, EHEC survival may enhance inflammatory responses responsible for intestinal epithelial barrier disruption, which could lead to an increase of Shiga toxins entering the bloodstream. Second, as Shiga toxins are expressed and participate in bacterial survival in macrophages, the production of Shiga toxins within macrophages may be used to increase the toxin concentration in the bloodstream, as it was shown that bacteria residing in macrophages release these toxins (53). Understanding the interactions between host and pathogen is of fundamental importance in developing vaccines and other new therapeutic agents, particularly in the case of E. coli O157:H7, as no effective treatment is presently available for humans infected with this bacterium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, EHEC survival may enhance inflammatory responses responsible for intestinal epithelial barrier disruption, which could lead to an increase of Shiga toxins entering the bloodstream. Second, as Shiga toxins are expressed and participate in bacterial survival in macrophages, the production of Shiga toxins within macrophages may be used to increase the toxin concentration in the bloodstream, as it was shown that bacteria residing in macrophages release these toxins (53). Understanding the interactions between host and pathogen is of fundamental importance in developing vaccines and other new therapeutic agents, particularly in the case of E. coli O157:H7, as no effective treatment is presently available for humans infected with this bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…Binding at the follicle-associated epithelium results in the rapid contact of E. coli O157:H7 with underlying human macrophages; however, there is very little information available about the interaction between EHEC and these cells. The interaction between EHEC and murine macrophages was investigated, and it was shown that phagocytosis of EHEC by murine macrophages caused actin rearrangements surrounding the phagosome; EHEC was rapidly killed, and high levels of Shiga toxins were produced (53). However, to our knowledge, the interaction between EHEC and human macrophages has not been investigated.…”
mentioning
confidence: 99%
“…Activation of inflammatory cascades such as increased IL-1β production has previously been demonstrated in macrophages in EHEC infection (20). Thus, we investigated key components of neuroinflammation such as tumor necrosis factor α (TNF-α) and IL-1β in EHEC patients and controls.…”
Section: Resultsmentioning
confidence: 95%
“…Shiga toxin-producing bacteria and Shiga toxins can be detected by different methods, including enzyme-linked immunosorbent assays (ELISA), cytotoxicity assays, and polymerase chain reaction (PCR) [20,50,51]. Also, flow cytometry detection of Shiga toxins bound to polymorphonuclear leukocytes was reported to be a rapid, simple, and sensitive method of detecting circulating Shiga toxins and diagnosing STEC infections [52].…”
Section: Detection Of Shiga Toxinsmentioning
confidence: 99%
“…If the epithelial cell barrier is disrupted, then macrophages can engulf the bacteria. Importantly, even when the bacteria are taken up and killed by the macrophages, these cells secrete toxin in the surroundings [51].…”
Section: Transport Of Shiga Toxin Across Epithelial Cellsmentioning
confidence: 99%